INSTRUCTIONAL DESIGN OF LINEAR EQUATIONS WITH ONE VARIABLE USING A BALANCING TOOL FOR GRADE VII - Novitasari, Ranny; Zulkardi, Zulkardi; Darmawijoyo, Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
This research is a design research that aims to generate the learning trajectory of students in linear equations with one variable using a balancing tool. Resolve problem related to linear equations with one variable is one of the basic competencies in the high school curriculum for grade 7. But in fact, many students are having difficulty in solving the story problem on linear equations with one variable, so that causing students to make mistakes. Mathematical learning should begin with the introduction of contextual problems. By posing contextual problems, learners are gradually guided to master mathematical concepts. One approach to mathematics learning in accordance with that is the Indonesian Realistic Mathematics Education (PMRI). Researchers designed the hypotetical learning trajectory to be used as guidelines for teachers during the learning process. The appropriate starting point for studying the concept of linear equations with one variable is about balance activity. The contextual problem chosen by researcher is about using a balancing tool. The results showed that the learning of linear equations with one variable using PMRI can help students develop from the informal to the formal stage of mathematics and can be used as alternatives in learning.